The Effect of Leadership Style, Work Conflict and Work Stress on Employee Performance with Organizational Commitment as Intervening Variables - Febriyanti Nugrahayu; Nurdin Brasit; Andi Reni (SEIKO : Journal of Management & Business, 2023)
The purpose of this study is to ascertain the impact of management, the workplace, and compensation on the performance and work ethics of South Sulawesi High Prosecutor's Office employees. Additionally, this study seeks to understand how employee performance is impacted by workplace discipline. The moderating impact of work discipline on executive relationships, the workplace, compensation, and nurse performance is another goal of this study. The 97 employees of the South Sulawesi High Court are the subjects of this quantitative study, which is conducted on a group of people. A structured questionnaire or questionnaire was used for data collection, and Partial Least square (PLS) was used for data analysis. The findings of this study suggest that leadership, the workplace, and compensation all significantly and favorably affect work discipline. It was discovered that the work discipline variable significantly and favorably affected employee performance. This study also demonstrates that leadership, work environment, and pay have negligible or no positive effects on employee performance. According to the research, work discipline does not act as a moderator in the relationship between leadership, work environment, and compensation for employee performance. Keywords: Leadership, Work Environment, Remuneration, Work Discipline, Employee Performance.